Towards a paradigm shift: incorporating indigenous epistemologies in primary school education - Machingure, Viola; Mutemeri, Judith (C. C. Wolhuter, 2016)
The glaring marginalization of African knowledge systems from most, if not all, African curricula is no accident of history, but a deliberate process undertaken during Africa's colonization to subjugate its people. This has had far reaching repercussions on the child and his schooling, where the child was forced to operate in two parallel world-views. The purpose of this paper is to first, describe and define the African world-view as experienced in the home. Secondly, the paper highlights the great divide that there is between the home and the school and the catastrophes that the child finds himself in. Finally, the paper suggests way forward for primary school education.